Designing mascot character based on believable agent framework - Ardhianto, Peter; Aryani, Tabita Nani; Utami, Maya Putri (Gelar: Jurnal Seni Budaya, 2024)
Utilizing mascots as an extension of the brand to reach the target audience is one strategy in visual branding that has proven its effectiveness. Mascots with solid characters can build consumer trust and are even more impressive than other visual identities. However, currently, very few mascot design methods or steps lead to the creation of a mascot that is both convincing and an agent of the institution it represents. This research highlights the convincing agent design process as the primary basis for designing mascot designs. This research uses the theory of believable agents, which includes seven dimensions: personality, emotions, self-motivation, change, social interaction, consistency of expression, and the illusion of life. These seven theories will be supported by the results of the questionnaires. The questionnaire results found that credible and trustworthy agents should have a friendly personality, which can be seen from their facial expressions, body movements, and the way they present themselves. The research results confirm that the seven dimensions of a trustworthy agent can be applied to mascot design that prioritizes the formation of a unique and distinctive personality. Mascots will be perceived as genuine individuals with specific characteristics that appear in the way they act (behavior), the way they think (think), and the way they feel (emotions). The results of this research provide a bridge for designers to consider ideas up to the mascot design stage.